Enhanced mud-resistant polycarboxylic acid additive and preparation method thereof

By using a polycarboxylic acid additive with a three-layer polymer nanoparticle structure and combined with conventional polycarboxylic acid, the problem of degradation of polycarboxylic acid dispersion and slump retention ability in materials with high mud content is solved, and the concrete strength and durability are improved.

CN119505115APending Publication Date: 2025-02-25JIANGSU SOBUTE NEW MATERIALS CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311086561.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When using materials with high mud content, the dispersion and slump retention ability of polycarboxylic acid water reducing agent will be negatively affected by the soil, resulting in a decrease in the strength and durability of the concrete.

Method used

Polycarboxylic acid additives with three-layer polymer nanoparticle structure are used in combination with conventional polycarboxylic acids. The nanoparticles of this additive are composed of a core layer, an inner shell layer and an outer shell layer. They are prepared by aqueous emulsion polymerization to ensure that the polycarboxylic acid molecules are not adsorbed by the soil during the early stage of hydration and are released at appropriate times, playing a role in dispersing and enhancing the concrete structure.

Benefits of technology

Effectively resist the negative impact of soil on polycarboxylic acid, extend the retention time of concrete, enhance the strength and durability of concrete, and is suitable for the application of various blends and machined sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505115A_ABST
    Figure CN119505115A_ABST
Patent Text Reader

Abstract

The invention discloses an enhanced mud-resistant polycarboxylic acid additive and a preparation method thereof. The polycarboxylic acid auxiliary agent is a polymer emulsion, the polymer component of the polycarboxylic acid auxiliary agent is a three-layer polymer nanoparticle obtained through aqueous phase emulsion polymerization, the polymer nanoparticle structure sequentially comprises a core layer, an inner shell layer and an outer shell layer from inside to outside, and each layer is formed by polymerization induced self-assembly of corresponding polymers. The polycarboxylic acid additive is compounded with conventional polycarboxylic acid for use, so that in concrete using a material with relatively high mud content, the initial dispersing capacity of the polycarboxylic acid cannot be influenced, and the slump retaining time of the concrete can be prolonged by 1-3 hours by slowly releasing polycarboxylic acid molecules. Meanwhile, the polycarboxylic acid additive can improve the internal structure of the concrete and solve the problem that the strength of the concrete is reduced due to too high mud content; and the production process adopts a one-pot method, is green and environment-friendly, and is easy to realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and specifically relates to a polycarboxylic acid additive which can be used in combination with a polycarboxylic acid water reducer to enhance the strength of concrete and reduce the negative impact of soil in sand and gravel on polycarboxylic acid, and a preparation method thereof. Background Art

[0002] Polycarboxylic acid water reducer is the most widely studied and applied concrete admixture. When the workability of concrete remains unchanged, the addition of polycarboxylic acid can effectively save cement, reduce water consumption and improve concrete strength. Therefore, polycarboxylic acid superplasticizer is hailed as the third major revolution in concrete technology after reinforced concrete and prestressed concrete. In terms of molecular structure, polycarboxylic acid is a comb-shaped polymer, which consists of a main chain rich in carboxylic acid groups and polyether side chains. The carboxylic acid groups on the main chain can be directional adsorbed on the surface of positively charged cement or cement hydrates, while the polyether side chains stretch in the solution to form a hydration layer to provide spatial repulsion to prevent cement agglomeration. Therefore, this structure gives polycarboxylic acid a strong ability to disperse cement particles. In 1981, T. Hirata of Japan Catalyst Co., Ltd. applied for the first patent on polycarboxylic acid (JP842022 (S59-018338)). Since then, major universities and enterprises have begun to study polycarboxylic acid, and thousands of patents related to polycarboxylic acid products are published every year.

[0003] In order to reduce carbon emissions, we have to use some relatively poor quality materials that were rarely used in the past, such as some industrial waste slag admixtures, machine-made sand, etc. Especially machine-made sand, it is expected that it will occupy more than 50% of the national sand market in the next five years. In the manufacturing process of machine-made sand, it will be mixed with a high content of soil (the main components are montmorillonite, kaolin, etc.) which is difficult to remove. Compared with cement particles, these soils can adsorb polycarboxylic acid molecules better, resulting in the polycarboxylic acid molecules that could have provided dispersion ability being ineffectively adsorbed by the soil, and the water-reducing and slump-preserving abilities of polycarboxylic acid are greatly lost. In addition, the introduction of soil also affects the microstructure of concrete, resulting in a significant decrease in its strength and durability. Therefore, there is an urgent need for a polycarboxylic acid product that is suitable for various admixtures and machine-made sand applications and has the functions of increasing strength and resisting mud.

[0004] Researchers have conducted a lot of research on how to improve the strength of concrete. One of the most popular methods is to introduce polymer particles (emulsion or dry powder) into concrete, such as patents CN201410693203.3, CN202011594789.X, CN201610888586.9, etc. There are related reports. As an admixture, polymer particles can improve the bonding between concrete components and fill the pore structure of concrete. The dispersion and film formation of polymer particles are the main reasons for their enhancement. There is a physical effect or partial chemical bonding between the polymer and the inorganic material, that is, the polymer modifies the concrete microstructure in the form of particles or films, and can also form a chelate with a more compact structure combined by coordination. For example, the introduction of active groups such as -OH, -COOH, and -COOR in polymer particles can produce coordination with cement hydration products, change the bond type of cement materials mainly based on silicon oxygen bonds, and add organic carbon hydrogen bonds. The bond type is significantly enhanced, forming a double-set network structure that is stacked and staggered, improving the bonding between interfaces and increasing the interface fracture energy and toughness (Bulletin of the Chinese Ceramic Society, 2014, 33, 365). At the same time, polymer particles also have a wrapping effect, which can protect their internal structure from being affected by the environment in cement, and then slowly release the internal molecules at the right time, which is consistent with the slow release mechanism of polycarboxylic acid collapse-preserving agents. Therefore, polymer nanoparticles have been proven to be suitable for the development of collapse-preserving polycarboxylic acids, as described in detail in the literature Construction and Building Materials, 290 (2021), 123149. In principle, if the ineffective adsorption of polycarboxylic acid molecules by soil can be avoided in the early stages of hydration, the negative impact of soil can theoretically be resisted. Therefore, it is theoretically feasible to develop mud-resistant polycarboxylic acid products using the outer layer protection formed by polymer nanoparticles.

[0005] In summary, the present invention designs a polymer nanoparticle, which can be used as an additive in combination with polycarboxylic acid in practical applications to improve the anti-mud performance of polycarboxylic acid and enhance the strength of concrete. Summary of the invention

[0006] In view of the above problems, the present invention provides a polycarboxylic acid additive, which is used in combination with conventional polycarboxylic acids. In concrete using materials with a high mud content, it not only does not affect the initial dispersibility of polycarboxylic acids, but also prolongs the collapse time of concrete by 1 to 3 hours by slowly releasing polycarboxylic acid molecules. At the same time, the polycarboxylic acid additive can also slowly release polymer particles containing different functional groups such as carboxyl, amide, and sulfonic acid, which can produce physical and chemical effects with the microstructure of concrete, thereby improving the internal structure of concrete and compensating for the problem of reduced concrete strength caused by excessive mud content.

[0007] The present invention provides an enhanced anti-mud polycarboxylic acid additive, which is a polymer emulsion, and its polymer component is a three-layer polymer nanoparticle obtained by aqueous emulsion polymerization, and the actual solid content is 20wt%-40wt%;

[0008] The polymer nanoparticle structure includes a core layer, an inner shell layer, and an outer shell layer from the inside to the outside, and each layer is self-assembled by a corresponding polymer through polymerization induction;

[0009] The constituent polymer of the core layer of the polymer nanoparticle has the following general structural formula (I), and the wavy line structure refers to other segments having the molecular structure shown in the general formula (I), indicating that the structure is a three-dimensional high molecular cross-linked polymer:

[0010]

[0011] The constituent polymer of the inner shell layer of the polymer nanoparticle has the following general structural formula (II):

[0012]

[0013] Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO, BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer segments respectively, the weight average molecular weight of each segment ranges from 1000 to 3000, 800 to 2200, 200 to 500 respectively, each segment is block or randomly distributed, X is other molecular structures except carbon-carbon double bonds in ester-type cross-linking monomers, and the wavy line structure refers to other segments having the molecular structure shown in general formula (II), indicating that the structure is a three-dimensional high molecular cross-linked polymer;

[0014] The polymer constituting the outer shell layer of the polymer nanoparticle has the following general structural formula (III):

[0015]

[0016] Wherein, R3 is -H or -CH3, R4 is a C1-C4 alkyl group, Y is other molecular structures except the carbon-carbon double bond in the ester-type cross-linking monomer, and the wavy line structure refers to other segments having the molecular structure shown in the general formula (III), indicating that the structure is a three-dimensional high molecular cross-linked polymer;

[0017] The ester-type cross-linking monomer structure contains at least two polymerizable double bonds and a hydrolyzable ester group.

[0018] The working principle of the polycarboxylic acid auxiliary agent of the present invention to play the reinforcing and anti-mud function is as follows: after being added into cement paste, the outer shell layer protects its internal structure so that it will not be quickly adsorbed by cement or soil. After the outer shell layer is gradually destroyed by the alkaline environment of cement, the polycarboxylic acid molecules constituting the inner shell layer are gradually slowly released. At this time, most of the soil has been covered by cement hydrates, so the polycarboxylic acid molecules are adsorbed on the cement hydrates to play a dispersing role, thereby overcoming the adverse effect of soil on the dispersion of the paste; when the inner shell layer is completely hydrolyzed and released, the nanoparticles of the core layer are "exposed". Since the nanoparticles contain functional groups such as amide, sulfonic acid, and carboxyl, they can react physically and chemically with the structure of concrete to form an organic-inorganic hybrid structure, thereby increasing their bond breaking energy and thus enhancing the strength of the concrete.

[0019] The polycarboxylic acid additive of the present invention is prepared by semi-continuous seed emulsion polymerization. First, core layer nanoparticles are prepared by monomer emulsion polymerization as seeds for subsequent reactions. Then, through subsequent monomer dropwise reaction, the newly formed polymer "accumulates" on the seeds to form an inner shell layer and an outer shell layer in sequence. The reaction process of the preparation process of the polycarboxylic acid additive nanoparticles is as follows: Figure 2 shown.

[0021] The raw material monomers used for preparing the core layer are styrene, divinylbenzene, maleic anhydride and 2-acrylamide-2-methylpropanesulfonic acid, and the mass ratio of the usage is 50-100:2-5:25-40:15-35;

[0022] The raw material monomers used for preparing the inner shell layer are polyether, acrylic acid, styrene, and ester type crosslinking monomers, and the mass ratio of the usage is 80-100:10-25:2-5:2-5;

[0023] The raw material monomers used for preparing the outer shell layer are unsaturated ester, styrene, and ester-type crosslinking monomer, and the mass ratio of the usage is 100-150:10-20:2-5;

[0024] The ester type crosslinking monomer used in the outer shell layer is the same as that in the inner shell layer.

[0025] In the three-layer polymer nanoparticles of the present invention, the mass ratio of the core layer, the inner shell layer and the outer shell layer is 5-15:80-120:8-18, and the final three-layer polymer nanoparticles have a solid content of 20-40wt% and a particle size of 40-80nm.

[0026] The raw material monomer polyether used for preparing the inner shell layer is an addition product of unsaturated alcohol and alkylene oxide, and has the following structural formula (IV):

[0027]

[0028] Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO and BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer chain segments, respectively, the weight average molecular weight of each chain segment ranges from 1000 to 3000, 800 to 2200 and 200 to 500, respectively, and each chain segment is block or randomly distributed.

[0029] The ester-type cross-linking monomer structure contains at least two polymerizable double bonds, which can cross-link the synthesized linear-comb polycarboxylic acid into a three-dimensional shape to facilitate the formation of stable nanoparticles. At the same time, the structure contains a hydrolyzable ester group, which can hydrolyze the three-dimensional polymer into a linear-comb shape of a common polycarboxylic acid in the alkaline environment of cement, thereby exerting a dispersing effect.

[0030] The ester type crosslinking monomer is specifically selected from any one of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, 1,6-ethylene glycol diacrylate, allyl acrylate, and diallyl maleate.

[0031] The unsaturated ester monomers in the raw material monomers used for preparing the outer shell layer are selected from any one or more of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl (meth)acrylate.

[0032] The preparation method of the polycarboxylic acid additive of the present invention can be specifically divided into the following three steps:

[0033] (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, water, an emulsifier, an oxidant, styrene, divinylbenzene, maleic anhydride and 2-acrylamide-2-methylpropanesulfonic acid are added to the four-necked bottle, and the mixture is stirred and dispersed uniformly at a constant speed for pre-emulsification. After a stable emulsion is formed, the temperature is raised to 30-70° C., and the first batch of reducing agent aqueous solution is added dropwise for 1-2 h. After the addition is completed, the mixture is kept warm for 0.5 h to obtain a seed emulsion, which is the core layer of the polymer nanoparticles.

[0034] (2) Preparation of the inner shell layer: Add a polyether monomer to the core layer emulsion prepared in step (1) and stir evenly, then dropwise add a monomer solution consisting of acrylic acid, styrene, and an ester-type crosslinking monomer and a second batch of reducing agent aqueous solution for 2 to 4 hours. After the dropwise addition is completed, heat-retaining and reacting for 0.5 hours to obtain a core-shell seed emulsion;

[0035] (3) Preparation of the outer shell layer: To the core-shell seed emulsion prepared in step (2), a monomer solution consisting of unsaturated ester, styrene, and ester-type crosslinking monomer and a third batch of reducing agent aqueous solution are added dropwise for 0.5 to 1 h. After the addition is completed, the reaction is kept warm for 0.5 h to obtain a three-layer polymer nanoparticle emulsion, which is the polycarboxylic acid adjuvant described in the present invention.

[0036] The emulsifier in step (1) is selected from any one of sodium dodecyl sulfate, sodium dodecyl sulfonate, OP-7, OP-10, OP-15, and OP-20, and the amount of the emulsifier accounts for 0.02 to 0.1% of the total mass of the reaction system in step (1).

[0037] The oxidant and the reductant together constitute a redox initiator, the oxidant is selected from any one of hydrogen peroxide, ammonium persulfate, and potassium persulfate, and the amount of the oxidant accounts for 0.05-0.15% of the total mass of the reaction system in step (1); the reductant is selected from any one of L-ascorbic acid, Rongalite, sodium sulfite, and sodium bisulfite, and the total amount of the reductant accounts for 30-75% of the mass of the oxidant, and then added dropwise in batches.

[0038] The polycarboxylic acid additive of the present invention needs to be compounded with conventional polycarboxylic acid water reducer, and the dosage is 10-30% of the mass of the polycarboxylic acid water reducer. If the dosage is too low, the enhancement and anti-mud function will not be exerted, and if the dosage is too high, the dispersibility of polycarboxylic acid will be affected.

[0039] The polycarboxylic acid finished product with the polycarboxylic acid additive of the present invention can be mixed with other commercially available plasticizers, such as wood sulfonates, naphthalene sulfonates, polycarboxylates, etc., and can also be used after adding air entraining agents, retarders, early strength agents, expansion agents, viscosity enhancers, shrinkage reducers and defoamers.

[0040] The polycarboxylic acid auxiliary agent of the present invention is used in combination with polycarboxylic acid, and its beneficial effects are as follows:

[0041] (1) It can resist the negative impact of soil in sand and gravel aggregates on polycarboxylic acid, and is particularly suitable for solving the problem of rapid loss of concrete slump caused by the use of inferior glue and machine-made sand.

[0042] (2) It is less sensitive to cement types and can enhance the adaptability of polycarboxylic acid.

[0043] (3) Enhance the strength of concrete.

[0044] (4) The production process adopts a one-pot method, which allows continuous production in the same reactor. It is highly efficient, does not use organic solvents, is environmentally friendly, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1This is a schematic diagram of the structure of the polycarboxylic acid auxiliary agent nanoparticles of the present invention. Figure 2 This is a reaction flow chart of the preparation process of polycarboxylic acid additive nanoparticles.

[0046] in, Figure 1 The labels are: 1 is the core layer, 2 is the inner shell layer, and 3 is the outer shell layer. DETAILED DESCRIPTION

[0047] The following examples describe in more detail the preparation process of the polycarboxylic acid adjuvant of the present invention. These examples are given in an illustrative manner, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, but these examples do not limit the scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

[0048] In the embodiments of the present invention, the codes of some raw materials used are shown in the following table.

[0049] Table 1 Raw material names and codes

[0050]

[0051]

[0052] The solid content of the nanoparticles synthesized in the embodiment of the present invention was measured after drying the water in a high-temperature blast drying oven, and the particle size was tested by a dynamic light scattering instrument (DLS, ALV / CGS-3, Germany) with a test laser wavelength of 610 nm and a test angle of 90°.

[0053] Example 1

[0054] A method for preparing an enhanced anti-mud polycarboxylic acid additive is specifically divided into the following three steps:

[0055] (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, 4975.7 parts of water, 4.5 parts of SDS, 8.3 parts of HP, 88.3 parts of St, 3.2 parts of DVB, 27.8 parts of MAH and 29.1 parts of AMPS were added to the four-necked bottle, and the mixture was stirred and dispersed uniformly at a speed of 500 rpm for pre-emulsification. After a stable emulsion was formed, the mixture was heated to 30° C. and a reducing agent aqueous solution prepared by mixing 4.5 parts of VC and 130.5 parts of water (this reducing agent solution is used together in the three steps) was added dropwise at a fixed speed for 1 hour. After the addition was completed, the mixture was kept warm for 0.5 hour to obtain a seed emulsion, which is the core layer of the nanoparticles.

[0056] (2) Preparation of inner shell layer: Add 746.8 parts of polyether monomer A-EO2000-PO850-BO350 (A represents that the polyether is obtained by epoxy addition of allyl alcohol, and the number represents the molecular weight of the corresponding segment) to the core layer emulsion prepared in step (1), stir evenly, then dropwise add a monomer solution consisting of 203 parts of AA, 36 parts of St, and 25.5 parts of EGDA and a reducing agent aqueous solution, the dropwise addition time is 2.5 hours, and after the dropwise addition is completed, the reaction is kept warm for 0.5 hours to obtain a core-shell seed emulsion;

[0057] (3) Preparation of the outer shell layer: To the core-shell seed emulsion prepared in step (2), a monomer solution consisting of 123.2 parts of MA, 14.7 parts of St, and 3.0 parts of EGDA and a reducing agent aqueous solution were added dropwise for 0.5 h. After the addition was completed, the mixture was kept warm for 0.5 h to obtain three-layer nanoparticles, which are the polycarboxylic acid adjuvant of the present invention. The solid content was measured to be 20.3 wt %, and the particle size was measured by DLS to be 46.6 nm.

[0058] The synthesis methods of Examples 2 to 12 are consistent with those of Example 1, and the specific reaction conditions are listed in the following table. Tables 2, 3, and 4 are the types and amounts of the raw materials in steps 1, 2, and 3. Table 5 is the specific reaction temperature, dropwise addition time, solid content, product particle size, and other data in the examples.

[0059] Table 2 Raw materials and amounts used in step (1)

[0060]

[0061] Note: The unit of dosage is mass parts.

[0062] Table 3 Raw materials and amounts used in step (2)

[0063]

[0064]

[0065] Note: The first letter in the polyether category represents the unsaturated alcohol used as the initiator for preparing the polyether. A represents allyl alcohol, H represents methyl allyl alcohol, T represents isopentenyl alcohol, V represents diethylene glycol monovinyl ether, and HV represents 4-hydroxybutyl vinyl ether. The numbers represent the molecular weight of the EO, PO, and BO segments.

[0066] Table 4 Raw materials and amounts used in step (3)

[0067]

[0068] Table 5 Reaction conditions and solid content, particle size test data

[0069]

[0070]

[0071] In order to test the performance of the polycarboxylic acid auxiliary agent synthesized in the example, a sample of a polycarboxylic acid water-reducing agent commonly found on the market was synthesized in the comparative example to serve as a control sample for the subsequent application examples.

[0072] Comparative Example

[0073] 240 parts of H-EO2330 oxyethylene ether, 1.2 parts of 30wt% hydrogen peroxide and 240 parts of water were added to a four-necked flask equipped with a thermometer and a mechanical stirrer, and then stirred and heated to 45°C. At this temperature, a mixed solution consisting of 28.8 parts of AA, 0.92 parts of mercaptoethanol, 0.31 parts of VC and 30 parts of water was added dropwise for 3 hours. After the addition was completed, the temperature was kept for 1 hour. M was measured by gel permeation chromatography w The molecular weight distribution coefficient is 34100 and 1.64.

[0074] Application Examples

[0075] Application Example 1

[0076] In order to detect the anti-mud performance of the polycarboxylic acid additive of the present invention, according to the provisions of GB / T8077-2000 "Test Method for Homogeneity of Concrete Admixtures", the products synthesized in the embodiments of the present invention and the comparative examples were compounded and tested for the fluidity of the mortar containing montmorillonite. Test ratio: cement 594, montmorillonite 6, river sand 1300, water 252, water reducer dosage: comparative example 0.18%, the embodiment is compounded with the comparative example when used, the ratio is 0.15% of the comparative example + 0.03% of the embodiment. The test data is shown in Table 6. It can be seen from the data in the table that at the same dosage, the comparative example sample loses very quickly, and the fluidity is only 158mm at 60min, which is basically lost. For the same comparative example sample, after adding part of the embodiment sample, the initial dispersion is not affected at all, and the slump retention ability is greatly improved, and the fluidity is greater than 200mm at 120min. This shows that the polycarboxylic acid additive synthesized in the embodiment of the present invention is added to the conventional polycarboxylic acid water reducer, which can greatly improve the slump retention ability of the product.

[0077] Table 6 Test results of fluidity of cement mortar containing montmorillonite

[0078]

[0079]

[0080] Note: -- indicates loss of fluidity

[0081] Application Example 2

[0082] In order to detect the current situation that the polycarboxylic acid additive of the present invention is used in various admixtures and machine-made sand in the market at a high ratio, according to the provisions of GB / T8077-2000 "Test Method for Homogeneity of Concrete Admixtures", the products synthesized in the embodiments of the present invention and the comparative examples are compounded and tested for mortar fluidity. Test ratio: cement 400, mineral powder 50, fly ash 80, steel slag powder 50, machine-made sand 1200 (stone powder content 7%), water 245, water reducer dosage: comparative example 0.22%, when the embodiment is used, it is compounded with the comparative example, and the ratio is 0.17% of the comparative example + 0.05% of the embodiment. The test data is shown in Table 7. It can be seen from the data in the table that at the same dosage, the comparative example sample is initially small and loses very quickly, and the fluidity is completely lost at 40 minutes. For the same comparative example, after adding part of the embodiment sample, the initial dispersion increases by more than 20 mm, and after rapid loss at 20 minutes, the fluidity loss in the later period is extremely slow, and the fluidity is greater than 190 mm at 120 minutes. This indicates that the polycarboxylic acid additive synthesized in the embodiment of the present invention is added to the conventional polycarboxylic acid water reducer, which is very suitable for the current market situation of high admixture and high-speed machined sand.

[0083] Table 7 Test results of fluidity of machine-made sand mortar

[0084]

[0085]

[0086] Note: -- indicates loss of fluidity

[0087] Application Example 3

[0088] In order to detect the influence of the polycarboxylic acid additive of the present invention on the adaptability of polycarboxylic acid, according to the provisions of GB / T8077-2000 "Test Method for Homogeneity of Concrete Admixtures", the mortar fluidity test was carried out after compounding the products synthesized in the embodiments of the present invention and the comparative examples, and the cement type was changed during the test. Test ratio: cement 600, river sand 1300, water 252, water reducer dosage: comparative example 0.15%, when the embodiment is used, it is compounded with the comparative example, and the ratio is 0.12% of the comparative example + 0.03% of the embodiment. The test data is shown in Table 8. It can be seen from the data in the table that when different cements are used, the fluidity of the comparative example sample fluctuates between 205 and 301 mm, showing that it is highly sensitive to the cement type, and it is obviously unsuitable in Hailuohe Tianshan cement. For the same comparative example sample, after adding part of the embodiment sample, the fluidity is stable at 263 to 289 mm, and the fluctuation range is small, showing that the polycarboxylic acid additive of the embodiment can significantly improve the adaptability of the polycarboxylic acid product.

[0089] Table 8 Test results of fluidity of different types of cement mortar

[0090]

[0091]

[0092] Note: -- indicates loss of fluidity

[0093] Application Example 4:

[0094] Next, the performance of the polycarboxylic acid additive synthesized in the embodiment of the present invention in concrete was tested according to the method specified in GB8076-2008. Concrete mass mix ratio: cement 230, mineral powder 50, fly ash 45, machine-made sand 665, crushed stone 1225, water 185, the dosage was fixed at 0.16% during the comparative test, and the dosage was 0.13% comparative + 0.03% during the embodiment test. In addition, 0.04% sodium sugar was added to ensure appropriate coagulation performance. The concrete test data is shown in Table 9. It can be seen that, similar to the mortar results, the initial slump and expansion of the comparative and embodiment samples are not much different, but the comparative sample loses very quickly, and the embodiment sample has better loss and slump. From the perspective of compressive strength, the embodiment is significantly higher than the comparative example. At 28d, the embodiment is on average 4MPa higher than the comparative example. This shows that the polycarboxylic acid additive of the present invention is very suitable for machine-made sand concrete, which can not only effectively control the slump loss rate of concrete, but also significantly enhance the strength of concrete.

[0095] Table 9 Test results of machine-made sand concrete

[0096]

[0097]

Claims

1. An enhanced anti-mud type polycarboxylic acid additive, characterized in that: The polycarboxylic acid auxiliary agent is a polymer emulsion, the polymer component of which is a three-layer polymer nanoparticle obtained by aqueous emulsion polymerization, and the actual solid content is 20wt%-40wt%; The polymer nanoparticle structure includes a core layer, an inner shell layer, and an outer shell layer from the inside to the outside, and each layer is self-assembled by a corresponding polymer through polymerization induction; The constituent polymer of the core layer of the polymer nanoparticle has the following general structural formula (I), and the wavy line structure refers to other segments having the molecular structure shown in the general formula (I): The constituent polymer of the inner shell layer of the polymer nanoparticle has the following general structural formula (II): Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO, BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer segments respectively, the weight average molecular weight of each segment ranges from 1000 to 3000, 800 to 2200, 200 to 500 respectively, each segment is block or randomly distributed, X is other molecular structures except carbon-carbon double bonds in ester-type crosslinking monomers, and the wavy line structure refers to other segments having the molecular structure shown in general formula (II); The polymer constituting the outer shell layer of the polymer nanoparticle has the following general structural formula (III): Wherein, R3 is -H or -CH3, R4 is a C1-C4 alkyl group, Y is other molecular structures except the carbon-carbon double bond in the ester-type crosslinking monomer, and the wavy line structure refers to other segments having the molecular structure shown in the general formula (III); The ester-type cross-linking monomer structure contains at least two polymerizable double bonds and a hydrolyzable ester group.

2. The enhanced anti-mud polycarboxylic acid additive according to claim 1, characterized in that: The polycarboxylic acid auxiliary agent is prepared by semi-continuous seed emulsion polymerization. First, core layer nanoparticles are prepared by monomer emulsion polymerization as seeds for subsequent reactions. Then, through subsequent monomer dropwise reaction, the newly formed polymer "accumulates" on the seeds to form an inner shell layer and an outer shell layer in sequence.

3. The enhanced anti-mud polycarboxylic acid additive according to claim 2, characterized in that: The raw material monomers used for preparing the core layer are styrene, divinylbenzene, maleic anhydride and 2-acrylamide-2-methylpropanesulfonic acid, and the mass ratio of the usage is 50-100:2-5:25-40:15-35; The raw material monomers used for preparing the inner shell layer are polyether, acrylic acid, styrene, and ester type crosslinking monomers, and the mass ratio of the usage is 80-100:10-25:2-5:2-5; The raw material monomers used for preparing the outer shell layer are unsaturated ester, styrene, and ester-type crosslinking monomer, and the mass ratio of the usage is 100-150:10-20:2-5; The ester type crosslinking monomer used in the outer shell layer is the same as that in the inner shell layer.

4. The enhanced anti-mud polycarboxylic acid additive according to claim 3, characterized in that: In the three-layer polymer nanoparticles, the mass ratio of the core layer, the inner shell layer and the outer shell layer is 5-15:80-120:8-18, and the particle size of the finally obtained three-layer polymer nanoparticles is 40-80nm.

5. The enhanced anti-mud polycarboxylic acid additive according to claim 3, characterized in that: The polyether is an addition product of an unsaturated alcohol and an alkylene oxide, and has the following general structural formula (IV): Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO and BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer chain segments, respectively, the weight average molecular weight of each chain segment ranges from 1000 to 3000, 800 to 2200 and 200 to 500, respectively, and each chain segment is block or randomly distributed.

6. The enhanced anti-mud polycarboxylic acid additive according to claim 3, characterized in that: The ester type crosslinking monomer is specifically selected from any one of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, 1,6-ethylene glycol diacrylate, allyl acrylate, and diallyl maleate.

7. The enhanced anti-mud polycarboxylic acid additive according to claim 3, characterized in that: The unsaturated ester monomer is selected from any one or more of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl (meth)acrylate.

8. The method for preparing a polycarboxylic acid auxiliary agent for enhancing mud resistance according to any one of claims 1 to 7, characterized in that: The specific steps are as follows: (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, water, an emulsifier, an oxidant, styrene, divinylbenzene, maleic anhydride and 2-acrylamide-2-methylpropanesulfonic acid are added to the four-necked bottle, and the mixture is stirred and dispersed uniformly at a constant speed for pre-emulsification. After a stable emulsion is formed, the temperature is raised to 30-70° C., and the first batch of reducing agent aqueous solution is added dropwise for 1-2 h. After the addition is completed, the mixture is kept warm for 0.5 h to obtain a seed emulsion, which is the core layer of the polymer nanoparticles. (2) Preparation of the inner shell layer: Add a polyether monomer to the core layer emulsion prepared in step (1) and stir evenly, then dropwise add a monomer solution consisting of acrylic acid, styrene, and an ester-type crosslinking monomer and a second batch of reducing agent aqueous solution for 2 to 4 hours. After the dropwise addition is completed, heat-retaining and reacting for 0.5 hours to obtain a core-shell seed emulsion; (3) Preparation of the outer shell layer: To the core-shell seed emulsion prepared in step (2), a monomer solution consisting of unsaturated ester, styrene, and ester-type crosslinking monomer and a third batch of reducing agent aqueous solution are added dropwise for 0.5 to 1 h. After the addition is completed, the reaction is kept warm for 0.5 h to obtain a three-layer polymer nanoparticle emulsion, which is the polycarboxylic acid auxiliary agent.

9. The preparation method according to claim 8, characterized in that: The emulsifier in step (1) is selected from any one of sodium dodecyl sulfate, sodium dodecyl sulfonate, OP-7, OP-10, OP-15, and OP-20, and the amount of the emulsifier accounts for 0.02 to 0.1% of the total mass of the reaction system in step (1); The oxidant and the reductant together constitute an oxidation-reduction initiator, wherein the oxidant is selected from any one of hydrogen peroxide, ammonium persulfate, and potassium persulfate, and the amount of the oxidant accounts for 0.05-0.15% of the total mass of the reaction system in step (1); the reductant is selected from any one of L-ascorbic acid, Rongalite, sodium sulfite, and sodium bisulfite, and the total amount of the reductant accounts for 30-75% of the mass of the oxidant.

10. The method for applying the enhanced anti-mud polycarboxylic acid additive according to any one of claims 1 to 7, characterized in that: The polycarboxylic acid auxiliary agent needs to be compounded with a conventional polycarboxylic acid water-reducing agent, and the amount used is 10 to 30% of the mass of the polycarboxylic acid water-reducing agent.

Citation Information

Patent Citations

  • An admixture for improving the flexural and tensile strength of cement-based materials and its preparation method

    CN104446102B

  • Amphiphilic polycarboxylic acid cement dispersant and preparation method thereof

    CN106519151A

  • A particulate phosphonic acid-based superplasticizer, its preparation method and its application

    CN114685727B